2022
DOI: 10.14336/ad.2021.1122
|View full text |Cite
|
Sign up to set email alerts
|

The Homeostasis of Cartilage Matrix Remodeling and the Regulation of Volume-Sensitive Ion Channel

Abstract: Degenerative joint diseases of the hips and knees are common and are accompanied by severe pain and movement disorders. At the microscopic level, the main characteristics of osteoarthritis are the continuous destruction and degeneration of cartilage, increased cartilage extracellular matrix catabolism, decreased anabolism, increased synovial fluid, and decreased osmotic pressure. Cell volume stability is mainly regulated by ion channels, many of which are expressed in chondrocytes. These ion channels are close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Wu et al‘s study [ 111 ] showed that Drp1 knockout can inhibit mitochondrial autophagy in cells and consequently suppress apoptosis of retinal endothelial cells, thus alleviating diabetic retinopathy. Deng et al [ 112 ] suggested that mitochondrial volume homeostasis may be involved in the homeostasis of cartilage matrix metabolism and play an important role in the progression of arthritis.…”
Section: Implications Of Imbalance In Mitochondrial Volume Regulationmentioning
confidence: 99%
“…Wu et al‘s study [ 111 ] showed that Drp1 knockout can inhibit mitochondrial autophagy in cells and consequently suppress apoptosis of retinal endothelial cells, thus alleviating diabetic retinopathy. Deng et al [ 112 ] suggested that mitochondrial volume homeostasis may be involved in the homeostasis of cartilage matrix metabolism and play an important role in the progression of arthritis.…”
Section: Implications Of Imbalance In Mitochondrial Volume Regulationmentioning
confidence: 99%
“…Cartilage destruction begins when chondrocytes are stimulated by pro-inflammatory cytokines such as IL-1β, IL-6, IL-8 and tumor necrosis factor (TNF)-α ( 29 , 30 ). Disruption of cartilage stromal integrity is caused by increased catabolism/apoptosis of chondrocytes in articular cartilage and decreased chondrocyte anabolism ( 31 , 32 ). IL-1β and TNF-α are among the key pro-inflammatory cytokines involved cartilage destruction in OA ( 27 ).…”
Section: Molecular Landscape Of Oamentioning
confidence: 99%
“…IL-1β induced enzymes of the MMP family, mainly interstitial collagenase (MMP-1), streptoglobulinase-1 (MMP-3), and collagenase 3 (MMP-13). These enzymes affect the expression of cartilage collagen ( 24 , 36 ), thereby affecting the balance between cartilage matrix synthesis and catabolism, leading to degenerative cartilage diseases such as OA ( 32 ). In addition, IL-1β induces chondrocytes to produce ADAMTS metalloproteinases ( 36 ), which affects aggrecan expression and regulates cartilage metabolism ( 37 ).…”
Section: Molecular Landscape Of Oamentioning
confidence: 99%
“…Lubricin is a surface-active glycoprotein providing boundary lubrication and preventing cell and protein adhesion. This means that chondrocytes rely on a delicate anabolic and katabolic balance to maintain joint homeostasis [3]. Joint autophagy plays an important role in the orderly degradation and recycling of cellular and ECM components within the joint [4,5].…”
Section: Osteoarthritismentioning
confidence: 99%